Renal plasticity in response to feeding in the Burmese python, Python molurus bivittatus - Esbaugh, A.J.; Secor, S.M.; Grosell, M. (Comparative biochemistry and physiology. Part A, Molecular & integrative physiology, 2015)
Burmese pythons are sit-and-wait predators that are well adapted to go long periods without food, yet subsequently consume and digest single meals that can exceed their body weight. These large feeding events result in a dramatic alkaline tide that is compensated by a hypoventilatory response that normalizes plasma pH; however, little is known regarding how plasma HCO3− is lowered in the days post-feeding. The current study demonstrated that Burmese pythons contain the cellular machinery for renal acid–base compensation and actively remodel the kidney to limit HCO3− reabsorption in the post-feeding period. After being fed a 25% body weight meal plasma total CO2 was elevated by 1.5-fold after 1day, but returned to control concentrations by 4days post-feeding (dpf). Gene expression analysis was used to verify the presence of carbonic anhydrase (CA) II, IV and XIII, Na+ H+ exchanger 3 (NHE3), the Na+ HCO3− co-transporter (NBC) and V-type ATPase. CA IV expression was significantly down-regulated at 3dpf versus fasted controls. This was supported by activity analysis that showed a significant decrease in the amount of GPI-linked CA activity in isolated kidney membranes at 3dpf versus fasted controls. In addition, V-type ATPase activity was significantly up-regulated at 3dpf; no change in gene expression was observed. Both CA II and NHE3 expression was up-regulated at 3dpf, which may be related to post-prandial ion balance. These results suggest that Burmese pythons actively remodel their kidney after feeding, which would in part benefit renal HCO3− clearance.